Per and poly-fluoroalkyl substances (PFAS) as a contaminant of emerging concern in surface water: A transboundary review of their occurrences and toxicity effects - Podder, Aditi; Sadmani, A.H.M. Anwar; Reinhart, Debra; Chang, Ni-Bin; Goel, Ramesh (Journal of hazardous materials, 2021)
Per and poly-fluoroalkyl substances (PFAS) have been recognized as contaminants of emerging concerns by the United States Environmental Protection Agency (US EPA) due to their environmental impact. Several advisory guidelines were proposed worldwide aimed at limiting their occurrences in the aquatic environments, especially for perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA). This review paper aims to provide a holistic review in the emerging area of PFAS research by summarizing the spatiotemporal variations in PFAS concentrations in surface water systems globally, highlighting the possible trends of occurrences of PFAS, and presenting potential human health impacts as a result of PFAS exposure through surface water matrices. From the data analysis in this study, occurrences of PFOA and PFOS in many surface water matrices were observed to be several folds higher than the US EPA health advisory level of 70 ng/L for lifetime exposure from drinking water. Direct discharge and atmospheric deposition were identified as primary sources of PFAS in surface water and cryosphere, respectively. While global efforts focused on limiting usages of long-chain PFAS such as PFOS and PFOA, the practices of using short-chain PFAS such as perfluorobutanoic acid (PFBA) and perfluorobutane sulfonic acid (PFBS) and PFAS alternatives increased substantially. These compounds are also potentially associated with adverse impacts on human health, animals and biota. [Display omitted] •Global shift in use of PFAS was observed from western to eastern part of the world.•Use of long-chain PFAS decreased due to regulations promoting short-chain PFAS.•Most studies reported PFOS and PFOA occurrences over US EPA threshold of 70 ng/L.•Discharge from WWTP acts as primary direct emission source of PFAS in rivers.•Globally high PFAS concentrations were observed in China, Japan, Korea, Australia.